Price transparency in Singapore bond market. - Khoo, Hsien Long. (2008)
This report consists of a study on the issue of price transprarency in the bond market. An analysis of the issue in the Singapore context was done to see if price transparency could help boost liquidity in the local market.Recommendations on how to improve transparency are also included in this report.